2019
DOI: 10.1038/s41598-019-40227-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of the curry tree (Bergera koenigii L., Rutaceae) during leaf development

Abstract: The curry tree (Bergera koenigii L.) is a widely cultivated plant used in South Asian cooking. Next-generation sequencing was used to generate the transcriptome of the curry leaf to detect changes in gene expression during leaf development, such as those genes involved in the production of oils which lend the leaf its characteristic taste, aroma, and medicinal properties. Using abundance estimation (RSEM) and differential expression analysis, genes that were significantly differentially expressed were identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…In curry leaf ( Murraya koenigii ), genes encoded for terpene synthases were functionally characterized to ascertain their role in the synthesis of leaf volatiles by wide transcriptome studies ( Meena et al, 2017 ). Further studies unlock gene families for polyketide synthases, prenyltransferases, methyltransferases, and cytochrome P450s involved in the production of carbazole alkaloids and leaf development ( Meena et al, 2017 ; Shivakumar et al, 2019 ). A tissue-specific transcriptome identifies genes involved in terpenoid and phenylpropanoid metabolism in ferula species ( Amini et al, 2019 ).…”
Section: Transcriptomic Studies: Comprehensive and Quantitative Resou...mentioning
confidence: 99%
“…In curry leaf ( Murraya koenigii ), genes encoded for terpene synthases were functionally characterized to ascertain their role in the synthesis of leaf volatiles by wide transcriptome studies ( Meena et al, 2017 ). Further studies unlock gene families for polyketide synthases, prenyltransferases, methyltransferases, and cytochrome P450s involved in the production of carbazole alkaloids and leaf development ( Meena et al, 2017 ; Shivakumar et al, 2019 ). A tissue-specific transcriptome identifies genes involved in terpenoid and phenylpropanoid metabolism in ferula species ( Amini et al, 2019 ).…”
Section: Transcriptomic Studies: Comprehensive and Quantitative Resou...mentioning
confidence: 99%
“…Until this study, only a few nuclear genes, complete chloroplast genome 37 , and a transcriptome 38 in mature leaves had been sequenced for the curry tree; this study adds 57,383 newly sequenced transcripts (including multiple transcriptional isoforms of the same gene), contributing to a new understanding of the molecular genetics of the curry leaf development. 39 .…”
Section: Transcriptome Analysismentioning
confidence: 99%
“…Recently, temporal gene expression profiles that characterize the time-dynamics of expression of specific genes related to the secondary metabolites of plants have attracted increasing scientific attention (Li et al, 2016;Liu et al, 2015;Mueller, Chiou & Leng, 2008;Shivakumar, Johnson & Zimmer, 2019;Sweetman et al, 2012;Wong et al, 2017). For example, Li et al (2016) reported that Camellia sinensis leaf transcriptomes differed among three growth stages, which is also the case for differentially expressed unigenes related to metabolic pathways, biosynthesis of secondary metabolites, phenylpropanoid biosynthesis, and carbon fixation during photosynthesis.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Li et al (2016) reported that Camellia sinensis leaf transcriptomes differed among three growth stages, which is also the case for differentially expressed unigenes related to metabolic pathways, biosynthesis of secondary metabolites, phenylpropanoid biosynthesis, and carbon fixation during photosynthesis. Shivakumar, Johnson & Zimmer (2019) identified differentially expressed genes (DEGs) involved in oil production using transcriptome analysis of the leaves of Bergera koenigii at different developmental stages. However, the temporal patterns of the gene expression of polysaccharide synthesis in C. paliurus at different leaf developmental stages have not been reported so far.…”
Section: Introductionmentioning
confidence: 99%